Socio-religious transformations in Iscahuaca, a community victim of violence (Aymaraes, Apurímac): (Aymaraes, Apurímac) - Flores Lizana, Carlos (2001)
The author of this investigation was in the community of Iscahuaca from November 4, 1997 to June 26, 1998. Months during which the community was in full rainy season, from December to mid-April. This, on the one hand, made work difficult, especially to get around on foot, but it was important to see the community during the two most important climatic seasons in the Peruvian highlands, that is, from November to April, during rains, and from May to October, dry or summer time, although it is good to remember that there are always advances or delays in the beginning and end of these two great seasons.